Crisis Communication And Management On Food Recall In The Malaysian Food Industry - M.A. Kal-Kausar; N.H. Nurulhusna; A. Siti Mashitoh; Norhayati Rafida Abdul Rahim; Alina Abdul Rahim (IDOSI Publications, 2024)
Middle-East Journal of Scientific Research 13 (Approaches of Halal and Thoyyib for Society, Wellness and Health): 54-60, 2013